Experiências de discriminação racial entre estudantes universitários: percepções, implicações e efeitos. - Campos, Marcos Pires (2024)
Racial discrimination, although silent, has a devastating impact on the mental health of university students. This study aimed to analyze the racial discrimination experiences encountered by this group, investigating their stories and the effects of these experiences on mental health. Conducted at five higher education institutions in the northern region of Ceará, the study included 829 participants and employed a mixed, exploratory, and cross-sectional approach. In the quantitative phase, the Racial Discrimination Experiences Scale and the Mental Health Inventory (MHI-38) were used, while in the qualitative phase, 37 semi-structured interviews were conducted to deepen and contextualize the reported experiences. Quantitative data were analyzed using SPSS 20.0 software, and qualitative data were analyzed with IRaMuTeQ software. Results revealed that 71.5% of students reported experiencing some form of racial discrimination, with the university setting being the most common context (43.2%). Those who experienced discrimination showed significantly higher levels of psychological distress (mean of 75.4) compared to those who had not encountered such situations (48.2), as well as lower emotional well-being (55.6 versus 72.8), highlighting the association between prejudice and emotional impact. The research also indicated that 65% of students experienced some type of racial discrimination that directly affected their academic performance, generating feelings of devaluation and isolation. Daily microaggressions, although less evident, were highlighted as especially harmful to students' mental health. In light of these findings, the urgency of affirmative policies and institutional actions to combat racial discrimination and foster the transformation of universities into genuinely inclusive environments is underscored.